Clinical Relevance of Loneliness in Schizophrenia Patients - Windy Tiandini (Jurnal Psikiatri Surabaya, 2024)
Introductions: Loneliness is a subjective feeling that is described as a sense of isolation, a bad feeling about the quality and quantity of social relationships that has a major impact on mental health, well-being and quality of life. Social isolation is an important predictor of loneliness. Social isolation is often experienced by schizophrenia patients who experience alienation, social disconnection, limited access, and social support for their mental health. This study aimed to describe the relationship and its effect and factors related of loneliness and mental health, expecially in Scizophrenia patients. Methods: This study is a literature review that collects from various sources of scientific journals related to loneliness and its effect to Schizophrenia patients. Results: Lack of social interaction causes low or poor and vulnerable self-concepts experienced by schizophrenia patients, this is suspected of causing maladaptive cognition of oneself and others. Self-esteem that is seen as bad, hallucinations and delusions that are negative and self-critical reinforces negative self-concept. Schizophrenic sufferers tend to experience distortions related to self-confidence and their environment, they often think that they cannot be accepted by their environment and their environment rejects them. These increases feelings of loneliness and is thought to increase the incidence of psychotic symptoms. Conclusions: Social isolation and loneliness are important issues for schizophrenia patients because they can increase morbidity and mortality rates. Loneliness increases the incidence of auditory hallucinations with paranoid thinking, as well as negative beliefs about oneself and others in schizophrenia patients. Keywords: Schizophrenia, Mental Health, Loneliness